Effects of creatine supplementation on nociception in young male and female mice - Izurieta-Munoz, Haydee (Pharmacol Rep, 2017)
BACKGROUND: The objective of this study was to evaluate creatine as an anti-nociceptive compound in an animal model of thermal and inflammatory pain. Creatine has the structural potential to interact with acid-sensing ion channels (ASIC), which have been involved in pain sensation modulation. The hypothesis evaluated in this study was that creatine will interact with ASICs leading to decreased nociception. METHODS: Male and female C57BL/6J mice were fed with either a control diet or the control diet supplemented with creatine (6.25g/kg diet). After one week on the diet, the mice were tested for thermal hyperalgesia and inflammatory pain response. RESULTS: The latency to withdraw the tail during the thermal hyperalgesia test was unaffected by sex or diet. During the formalin test, males and females responded differently to the stimulus, and the female mice supplemented with creatine seemed to recover faster than the controls. To determine whether ASICs mediate the action of creatine, GMQ, an ASIC3 agonist, was injected in one paw and pain response was quantified. Females responded more strongly to GMQ injections, and all mice fed creatine had a decreased response to GMQ. CONCLUSIONS: These preliminary data suggest a potential effect of creatine on inflammation-based nociception that may be mediated via ASIC3. While preliminary, this study warrants further research on the potential of creatine as an analgesic and can serve as a stepping stone for the development of ASIC-based therapeutics.